Chapter 16. Islamic finance in the metaverse: meta-finance frameworks for supporting the growth of Shariah-compliant finance options in the metaspace - Katterbauer, Klemens (Islamic finance in the digital age, 2024)
The metaverse has emerged as a topic of paramount importance in recent years, functioning as a virtual universe where individuals and companies can interact. While the metaverses are still in their nascent stages, there has been a notable increase in interest and capital inflow into these virtual realms. For investors and participants focused on Shariah-compliant financial practices, this presents a considerable challenge due to the current lack of Islamic financing frameworks applicable to the metaverse. In our study, we have developed new frameworks for facilitating Shariah-compliant financing within the metaverse, highlighting the challenges and considerations necessary for establishing Shariah-compliant financial instruments in this context. Our framework adapts traditional Islamic financing options, such as Murabaha and Sukuk, to the metaverse context, ensuring that both contracting mechanisms and crypto-payments align with Shariah principles and support the unique environment of the metaverse. This framework marks a significant step forward in the development of Shariah-compliant financing models within the metaverse.